Controlled synthesis of two-dimensional (2-D) ultra-thin bismuth selenide (Bi2Se3) nanosheets by bottom-up solution-phase chemistry and its electrical transport properties for thermoelectric application - Bin Masood, Khalid; Kumar, Pushpendra; Giri, Rajiv; Singh, Jai (FlatChem, 2020)
Bismuth Selenide and associated compounds inheriting stacked layered structure represent a unique class of materials where bulks are insulating with conducting surfaces, best known as thermoelectric materials. The bottom-up solution-based approach is a convenient alternative producing ultrathin high quality two-dimensional Bi2Se3 nanosheets. The present investigation deals with glycol mediated synthesis of highly crystalline ultrathin Bi2Se3 nanosheets. The as-synthesized Bi2Se3 nanosheets exhibit a rhombohedral crystal structure with a substantial surface-to-volume ratio that can possess several potential applications. Besides, the ultrathin Bi2Se3 nanosheets produced herein, found to be n-type with robust spatial confinement of charge carriers advantageous for thermoelectric applications, delivering a high-power factor of 1.55 mu W/cmK(2) at 150 degrees C. The method demonstrates the generic feature of the solution phase technique for the synthesis of highly crystalline nanosheets allowing mass production of identical ultra-thin nanosheets that can be easily integrated into devices for several promising applications, including spintronics, energy storage, and topological quantum computation.
Keywords: Rhombohedral structure; Sheet-like structure; Thermoelectric nanomaterials; transmission electron microscopy; XPS Spectra